The Application Of Fetal Music Instrumental Tools Helps Fetal Growth In The Womb Of Pregnant Women At Posyandu Kemuning 1A Village Sukamakmur Ciomas - Handayani, Marybet Tri Retno; Wahyuni, Yuli; Elfrieda, Nyayu Siti Aminah Lily (Edumedia Solution, 2025)
Good fetal growth and development from the mother's womb can give birth to a generation that is healthy, intelligent, and of good character. Good fetal growth is influenced by several factors, namely: Good eating habits, hormonal factors and the environment around the fetus. One way to maximize the process of fetal growth in the womb is that the mother must play an active role in making efforts so that the baby grows actively when born later. one of them is to take advantage of fetal stimulation in the womb with a music sound player system for the fetus. Based on the 2023 questionnaire, there is a request from the community for the community service team to hold socialization and training on healthy heart and fetal development using the research results of the Lecturer which can be implemented in the 2024 community service program to implement the Fetal Music Instrumental Tool to Help Fetal Growth in the Womb of Pregnant Women at Posyandu Kemuning 1A Sukamakmur Village, Ciomas. This community service implements IKU 2, namely students gaining experience outside campus and IKU 3 where lecturers carry out activities outside campus and IKU 5, namely the work of lecturers is used by the community. In addition, this activity produces HAKI products, videos of activities, articles in various electronic media, and publications in community service journals.